Penambatan Molekuler Senyawa Bioaktif Daun Wungu (Graptophyllum Pictum (L) Griff) sebagai Inhibitor Tirosinase - Abdul Aziz; Dimas Andrianto; Mega Safithri (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Melasma is a skin disorder characterized by hyperpigmentation of the skin in areas exposed to sunlight and is included in the dominant skin disorder category in several countries. Meanwhile, data from the Food and Drug Administration shows that cosmetic products have progressed from 0.01% to 57.4% in terms of registered products over the last six years. Currently, melasma treatment and cosmetic applications as a whitening agent were carried out by regulating tyrosinase activity through the use of compounds such as kojic acid which poses a health risk. Therefore, it was necessary to have other alternatives that can regulate tyrosinase activity without harming health. This study aimed to determine inhibitory effects of wungu leaf (Graptophyllum pictum (L) Griff) bioactive component as an agent to inhibit tyrosinase activity through a molecular docking approach. A total of 28 wungu leaves bioactive components as a result of the analysis of Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detector (GC-FID) were tested for their inhibitory effects on tyrosinase activity. Linolenic acid and phytol were ligands that have the best inhibition on tyrosinase enzyme activity with affinity energies of -5.8 kcal/mol and -5.4 kcal/mol, respectively, and inhibition constants of 55.718 M and 109.489 M.